Congenital ingrown toenails. - Inalöz, H.S.; Harman, M.; Akdeniz, S.; Inalöz, S.S. (European Journal of Pediatric Dermatology, 1999)
A case of a 7 month old boy with bilateral symmetrical congenital hypertrophy of the lateral nail folds of the hallux is described. The types of ingrown nails in infancy are discussed. A partial remission of the disease after 6 months was observed.